One-Pot Synthesis of 2-Arylquinolines via in situ Acid Catalysis - Han, Qiang; Li, Shichen; Cai, Zepeng; Ding, Chengcheng; Feng, Lei; Ma, Chen (Synthesis, 2022)
A simple, efficient, and practical protocol is reported, allowing quick access to diverse 2-arylquinolines from 2-vinylanilines and benzyl halides. This reaction is additive and metal catalyst-free with only solvent needed. A preliminary mechanistic investigation discloses the driving force comes from the in situ released HBr, which catalyzes the subsequent cyclization. The present synthetic route featured high functional group tolerance and simple post-processing. A variety of 2-arylquinolines were obtained up to 96% yield.
Keywords: metal-catalyst free; additive free; 2-arylquinolines; in situ acid; 2-vinylanilines